Novel strategy and multi-scale modelling of integrated multifunctional composite for thermal protection under extreme environment. (5th June 2022) - Li, Weijie; Zhang, Zhongwei; Zhu, Mengdie; Zhang, Jun; Huang, Haiming; Liang, Jun
Highlights: Novel strategy for integrated multifunctional composite is proposed. A multi-scale computational modelling is established for integrated composite. Integrated composite has an overall 3-dimensional reinforcement. Integrated composite exhibits both thermal insulation and recession resistance. Abstract: In order to overcome the shortcomings of the heritage thermal protection materials with only a single function as well as the macroscopic evaluation method lacking the consideration of manufacture parameters, in this study, a novel strategy of integrated multifunctional composite with an overall 3-Dimensional reinforcement weave fabric and multifunctional zones was prepared, and a new multi-scale computational modelling for evaluating its thermal protection performance was established. The properties of constitute materials were characterized, as well as the thermal and ablative behavior of the integrated multifunctional composite were tested by oxyacetylene test. The new modelling took the detail weaving parameters as well as the physical and chemical mechanisms of the composite into consideration. The model was solved by our FORTRAN codes. The experimental and simulation results showed that this new integrated composite had high structural efficiency, thermal insulation and recession resistance. The multi-scale computational modelling can be applied on the evaluation of the performance of the integrated woven composite in a bottom-up manner, which gives a refined design method for thermal protection materials.